(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2010)
The peculiarities of the condensation reactions of 1-ethoxycarbonylcyclopentanone-2 with some binucleophils taking place with cycle opening have been studied. The reaction products have been investigated and possible reasons for obtaining anomalous products have been proposed. The double-stage methods for synthesis of target hard-to-reach heterocycles have been elaborated.